Implementasi Pebiasaan Kultum dalam Meningkatkan Self Confidence Siswa di SMA Islam Shafta Surabaya Ismy Masitha Hafidlotul Umamy - Umamy, Ismy Masitha Hafidlotul (Proceedings of Annual Islamic Conference for Learning and Management, 2025)
Abstrak This study aims to determine the implementation of the cultum (sermon) practice at SHAFTA Islamic High School in Surabaya and its impact on improving student self- confidence. This study used a qualitative approach with a descriptive approach. Data were obtained through observations of the cultum activities, interviews with Islamic Religious Education (PAI) teachers and students, and supporting documentation. The results indicate that the cultum activities were conducted routinely and in a structured manner after congregational prayers, with a rotation system in each class. This activity provided a space for students to practice public speaking, manage nervousness, and increase courage and self-confidence. Changes were seen in increased courage to perform, communication skills, active participation in learning, and students' responsibility in preparing themselves. Furthermore, the cultum activities also internalized Islamic values such as syaja'ah (religious conduct), amanah (trustworthiness), and politeness in speaking. Thus, the cultum practice proved to be an effective medium for increasing students' self-confidence while strengthening their religious character.